Mix Code in the Literary Work “O Ammalek” by Goenawan Monoharto - M. Arifin Zaidin; Nunung Supratmi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
“O Ammalek” is the name of the grandmother/mother. In the book “O Ammalek” reflects on reminiscing/memorabilia for the grandmother or mother who raised the author and this moment becomes information how meaningful life means with the presence of “O Ammalek” so that anyone for a mother is very multi-meaning in a life. Code-mixing is the process of transferring linguistic units from one language to another to broaden the language’s style or variety. Code-mixing is a component of sociolinguistics that occurs not only orally but also in writing. Language is a tool that humans use to express their thoughts and feelings. Language is a means of communication that is critical in the expression of the soul. The purpose of this study is to examine the structure, function, type, and elements that contribute to the creation of code-mixing in a collection of poems by Goenawan Monoharto, entitled “O Ammalek” (2020). Qualitative descriptive method was used in this study. The primary source of data for this study is Goenawan Monoharto’s poetry collection